Effects of common rice field weeds on the survival, feeding rate and feeding behaviour of the crayfish Procambarus clarkii - Quan Yuan (Nature Portfolio, 2021)
Abstract To check if it is possible for crayfish to reduce the weed biomass in a paddy field, we hypothesised that crayfish can feed on common weeds in a paddy field. The feeding ability of red swamp crayfish, Procambarus clarkii, males and females for 4 weeds, Ludwigia prostrata Roxb., Leptochloa chinensis (L.) Nees, Echinochloa crusgalli (L.) Beauv and Eclipta prostrata L., commonly found in rice–crayfish fields were evaluated using a quantitative feeding experiment and behaviour observation experiment. The results of the quantitative feeding and behaviour experiments were highly consistent. The P. clarkii gender and weed species had no interactive effects on survival rate, the daily feed intake (FI) and percentage of daily feed intake (PFI). The results of the quantitative feeding experiment showed that the FI and PFI values of both P. clarkii females and males were significantly higher in the P. clarkii feed group than in the weed treatment group. Both FI and PFI were significantly higher in the L. chinensis group than in the other treatment groups. The survival rate of P. clarkii was significantly lower in the E. crusgalli group than in the other treatment groups. The behaviour observation experiment showed that the feeding frequency and duration were in the order of L. chinensis > E. prostrata > L. prostrata > E. crusgalli. The results indicate that the P. clarkii specimens liked to eat L. chinensis (mean PFI was more than 2%), hardly fed on E. crusgalli.